Management of Complex Biliary Cases in A Tertiary Referral Setting: Real World Lessons and Their Role in Shaping Future Clinical Strategies - Lesmana, Cosmas Rinaldi Adithya; Paramitha, Maria Satya; Pratiwi, Yulia Estu; Lesmana, Laurentius Adrianto; Ho, Khek Yu (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Background: In the era of laparoscopic procedure, innovative non-surgical approaches have emerged for managing biliary tract disorders. Techniques such as therapeutic endoscopic retrograde cholangiopancreatography (ERCP) and interventional endoscopic ultrasound (EUS) are increasingly being utilized. However, a clear consensus on a stepwise approach to managing difficult biliary disorders remains elusive. Therefore, this study was performed to evaluate the impact of endoscopic approach management on the outcomes of complex biliary cases.Methods: A retrospective study was conducted using an endoscopy database over two-year period. The characteristics of the study subjects, including demography and clinical data, were presented descriptively. The technical success rate was defined as the completion of the procedure performed on the patients. A bivariate analysis was conducted to evaluate the outcomes of therapy.Results: Sixty-one subjects with similar proportions in malignant (44.3%) and non-malignant (55.7%) etiologies in this retrospective database study were considered as complex biliary cases. Among them, 16.4% underwent a combination of therapeutic ERCP and EUS in one session based on the complexity of the case. Additionally, 8.2% of the subjects underwent ERCP with additional single operator cholangioscopy procedure. One subject (1.6%) underwent a rendezvous ERCP procedure through a percutaneous approach, while 4.9% underwent EUS-guided biliary drainage procedure. This study revealed no significant association between all mortality outcomes and baseline characteristics of the patients. Furthermore, there were no significant associations between mortality and the need for re-intervention, post-procedural pain, or the occurrence of acute pancreatitis.Conclusion: Complex biliary cases require a good clinical approach algorithm to decide which procedure comes first based on a comprehensive evaluation consisting of the patient’s factor, expertise, cost, and the risk of complications.